An improved multiphase SPH algorithm with kernel gradient correction for modelling fuel–coolant interaction - Wang, Fang; Zhang, Zhi-Gang; Wu, Qi (Frontiers in Energy Research, 2023)
Fuel-coolant interaction (FCI) has a pivotal role in the development of core disruptive accident in sodium cooled fast reactor. The drastic deformation of multiphase interface in FCI is hard to deal with traditional grid method. In this paper, an improved multiphase smoothed particle hydrodynamics (SPH) algorithm corrected with kernel gradient correction (KGC) technique is presented for multiphase flow with large density ratio and complex interfacial behaviors. The density discontinuity across the multiphase interface is described with the use of special volume, which only depends on the position information of adjacent particles. This multiphase SPH algorithm, which is troubled by an unstable and mixed interface problem under a large density ratio, is significantly improved with KGC technique. The accuracy and robustness of the improved method are demonstrated in the numerical simulations of the deformation of a square droplet, Rayleigh-Taylor instability and a bubble rising in water. The verified corrected multiphase SPH is applied to simulate the hydrodynamic behaviors of general FCI and the interaction between fuel coated with stainless steel film and coolant. Boundary layer stripping, Rayleigh-Taylor instability and Kelvin-Helmholtz instability are observed as important mechanisms of hydraulic fracturing. The fragments’ distribution and the influence of stainless steel film are analyzed. The existence of stainless steel film has been shown to inhibit breakage.